Pengaruh Model Pembelajaran Mind Mapping Terhadap Kemampuan Menulis Teks Karya Ilmiah Siswa Kelas XI SMA Negeri 7 Palembang - Hidayat, Rian; Nufus, Hayatun; Agustina, Juaidah (ANTHOR: Education and Learning Journal, 2022)
The problem in this study is whether there is an influence of the Mind Mapping learning model on the ability to write scientific work texts of the type of article for class XI students of SMA Negeri 7 Palembang. The purpose of this study was to find out and describe the effect of the Mind Mapping learning model on the ability to write scientific work texts of the type of articles for class XI students of SMA Negeri 7 Palembang. The method used in this study was a quantitative method with a posttest Only Control Design and a study population of 288 and a sample of 78 people (39 class XI IPA 1 and 39 class XI IPA 2). Data collection techniques in this study used essay tests and interviews. The results showed that the t-count was 3.44 and t-table was 1.66. This indicated that t-count ≥ t-table. Thus it can be concluded that Ha is accepted and Ho is rejected. This means that the alternative hypothesis (Ha) in this study has the influence of the Mind Mapping learning model on the ability to write scientific texts of class XI students of SMA Negeri 7 Palembang.